UJI VALIDITAS MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI MENGGUNAKAN APLIKASI DORATOON GUNA MENINGKATKAN PEMAHAMAN PESERTA DIDIK - Siti Fatimatuz Zahro; Sumadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of learning media is crucial to support material delivery, enhance understanding, and encourage active student participation. In the digital age, leveraging technology, such as computers and interactive multimedia, is essential for creating engaging and effective learning experiences. This research aims to assess the validity level of animated video-based learning media using the Doratoon application for IPAS (Science, Social Studies, and Arts) subject on energy transformation in 4th-grade elementary school. The validation process involved language experts, material experts, and media experts, utilizing Likert scale validation sheets as instruments, focusing on content feasibility, design appearance, and technical ease of use. This study was conducted at UPT SD Negeri Jadi III, Tuban, involving 1 teacher and 25 4th-grade students. Data were collected through observation, interviews, questionnaires, test sheets, and validation sheets, then analyzed using descriptive quantitative methods. The validation results showed percentages of 88% from language experts, 88% from material experts, and 86% from media experts. The overall average validity reached 87.33%. Based on validity criteria, this learning media is categorized as "Very Valid" and is suitable for use in the learning process. It is hoped that this media can be a valid interactive alternative capable of optimizing students' critical thinking skills.